1999
DOI: 10.1046/j.1365-2346.1999.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ondansetron and droperidol for the prevention of post-operative nausea and vomiting after cholecystectomy and minor gynaecological surgery performed by laparoscopy

Abstract: The anti-emetic effects of ondansetron and droperidol were evaluated in 134 ASA Grade I and II female patients, scheduled for laparoscopic cholecystectomy and minor gynaecological laparoscopic surgery, who were randomly assigned to receive ondansetron 4 mg or droperidol 75 micrograms kg-1 intravenously immediately after induction of anaesthesia. The patients were assessed 1, 6, 12 and 24 h after surgery for intensity of nausea and number of vomiting episodes. In the case of the patients undergoing laparoscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Serotonin receptor antagonists (ondansetron, granisetron, tropisetron, dolasetron, and ramosetron) are highly efficacious for PONV following laparoscopic cholecystectomy [7,17,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Their actions involve both central and peripheral mechanisms in the control of nausea and vomiting.…”
Section: Serotonin Receptor Antagonists (Table 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Serotonin receptor antagonists (ondansetron, granisetron, tropisetron, dolasetron, and ramosetron) are highly efficacious for PONV following laparoscopic cholecystectomy [7,17,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Their actions involve both central and peripheral mechanisms in the control of nausea and vomiting.…”
Section: Serotonin Receptor Antagonists (Table 3)mentioning
confidence: 99%
“…Several investigations compared the prophylactic antiemetic efficacy of ondansetron with other commonly used and well-established antiemetics (e.g., droperidol and metoclopramide) in patients scheduled for laparoscopic cholecystectomy, and showed that preoperative prophylactic i.v. administration of ondansetron 4 mg was superior to droperidol 1.25 mg (75 µg/kg) or metoclopramide 10 mg [6,16,29,30]. However, Steinbrook et al reported that droperidol 0.625 mg plus metoclopramide 10 mg was more effective than ondansetron 4 mg for the prevention of PONV [31].…”
Section: Serotonin Receptor Antagonists (Table 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…6 In the presence of prophylactic antiemetics, the frequency decreased, but remained significant, within a range of 30% to 60% depending on the type of study. [7][8][9] Female gender, history of motion sickness or PONV, and a negative smoking history are also risk factors for PONV. 1,3 In general, these characteristics are not amenable to modification in the preoperative setting.…”
Section: Résultats : Aucune Différence Intergroupe N'a éTé Enregistrémentioning
confidence: 99%
“…Droperidol [ 8 ], a butyrophenone dopamine receptor antagonist, and ondansetron [ 9 , 10 ], a selective 5-hydroxytryptamine type-3 (5-HT3) receptor antagonist, are two widely used antiemetics in anesthesia that exhibit some efficacy in the prevention of PONV [ 11 14 ]. Over the decades, droperidol has been proven to be a highly effective antiemetic, without side effects such as arrhythmias, sedation, extrapyramidal symptoms and dizziness, especially with doses higher than 1.25 mg [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%